Increasing voluntary medical male circumcision uptake among adult men in Tanzania. (24th April 2017) - Wambura, Mwita; Mahler, Hally; Grund, Jonathan M.; Larke, Natasha; Mshana, Gerry; Kuringe, Evodius; Plotkin, Marya; Lija, Gissenge; Makokha, Maende; Terris-Prestholt, Fern; Hayes, Richard J.; Changalucha, John; et al.
Abstract : Objective: We evaluated a demand-creation intervention to increase voluntary medical male circumcision (VMMC) uptake among men aged 20–34 years in Tanzania, to maximise short-term impact on HIV incidence. Methods: A cluster randomized controlled trial stratified by region was conducted in 20 outreach sites in Njombe and Tabora regions. The sites were randomized 1 : 1 to receive either a demand-creation intervention package in addition to standard VMMC outreach, or standard VMMC outreach alone. The intervention package included enhanced public address messages, peer promotion by recently circumcised men, facility setup to increase privacy, and engagement of female partners in demand creation. The primary outcome was the proportion of VMMC clients aged 20–34 years. Findings: Overall, 6251 and 3968 VMMC clients were enrolled in intervention and control clusters, respectively. The proportion of clients aged 20–34 years was slightly greater in the intervention than control arm [17.7 vs. 13.0%; prevalence ratio = 1.36; 95% confidence intervals (CI):0.9–2.0]. In Njombe region, the proportion of clients aged 20–34 years was similar between arms but a significant two-fold difference was seen in Tabora region ( P value for effect modification = 0.006). The mean number of men aged 20–34 years (mean difference per cluster = 97; 95% CI:40–154), and of all ages (mean difference per cluster = 227, 95% CI:33–420) were greater in the intervention than control arm. Conclusion: The intervention was associated with a significant increase in the proportion of clients aged 20–34 years in Tabora but not in Njombe. The intervention may be sensitive to regional factors in VMMC programme scale-up, including saturation.